A Multicriteria Group Decision-Making Method Based on the Normal Cloud Model With Zadeh's Z -Numbers - Peng, Hong-Gang; Wang, Jian-Qiang (IEEE transactions on fuzzy systems, 2018)
Z -number is the general representation of real-life information with reliability, and it has adequate description power from the point of view of human perception. This study develops an innovative method for addressing multicriteria group decision-making (MCGDM) problems with Z -numbers under the condition that the weight information is completely unknown. Processing Z -numbers requires effective support of reliable tools. Then, the normal cloud model can be employed to analyze the Z -number construct. First, the potential information involved in Z -numbers is invoked, and a novel concept of normal Z + -value is proposed with the aid of the normal cloud model. The operations, distance measurement, and power aggregation operators of normal Z + -values are defined. Moreover, an MCGDM method is developed by incorporating the defined distance measurement and power aggregation operators into the MultiObjective Optimization by Ratio Analysis plus the Full Multiplicative Form. Finally, an illustrative example concerning air pollution potential evaluation is provided to demonstrate the proposed method. Its feasibility and validity are further verified by a sensitivity analysis and comparison with other existing methods.